2005
DOI: 10.1016/j.pain.2005.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of couple congruence on pain, interference, and disability

Abstract: Couple congruence on ratings of pain severity and disability were examined using hierarchical linear modeling. Older community Individuals with Chronic Pain (ICPs) and their spouses completed the Multidimensional Pain Inventory (pain severity, interference, negative spouse responses to pain), Sickness Impact Profile (physical disability, psychosocial disability), and the Mood and Anxiety Symptom Questionnaire (psychological distress). Both spouses reported on ICPs' pain and disability as well as their own psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 55 publications
8
87
1
Order By: Relevance
“…Similarly, solicitous responses to pain behaviour did not influence the relationship between pain and patient adjustment. Contrary to previous findings in the chronic pain literature [9][10][11][12], solicitous responses and distracting spousal responses were not significantly associated with measures of physical and mental HRQL, disability and depressive symptoms. This difference may be the result of random sampling differences (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, solicitous responses to pain behaviour did not influence the relationship between pain and patient adjustment. Contrary to previous findings in the chronic pain literature [9][10][11][12], solicitous responses and distracting spousal responses were not significantly associated with measures of physical and mental HRQL, disability and depressive symptoms. This difference may be the result of random sampling differences (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Much of this research has examined partners' responses to pain communication (Romano, Jensen, Turner, Good, & Hops, 2000;Romano, Turner, Friedman, & Bulcroft, 1991;Romano et al, 1992;Romano et al, 1995). Spouses often make errors when estimating the pain and disability of persons with pain (Cano, Johansen, & Franz, 2005;Cano, Johansen, & Geisser, 2004b;Clipp & George, 1992;Miaskowski, Zimmer, Barrett, Dibble, & Wallhagen, 1997). The assumption in the pain field has been that each spouse shares the same symbol system, which may not always be the case as in a husband who values visual symbols of pain and a wife who primarily uses verbal symbols.…”
Section: Pain Communication 52mentioning
confidence: 99%
“…There is more research comparing patient and spouse perceptions of patient pain severity and interference in life activities due to pain (or a similar concept called pain related disability) than on patient and spouse perceptions of spouse responses to pain. The majority of past research reports that spouses typically overestimate patient pain (Cano et al, 2004b;Cremeans-Smith et al, 2003;Elliot et al, 1996;Miaskowski et al, 1997;Riemsma et al, 2000;Yeager et al, 1995), although a multilevel modeling study showed that there were no group differences between the individuals with pain and their spouses on perceptions pain severity (Cano et al, 2005). Moreover, spouses have been shown to overestimate disability associated with cancer pain (Elliot et al, 1996) and underestimate disability associated with musculoskele-tal pain (Cano et al, 2004b(Cano et al, ,2005.…”
Section: Pain Severity and Interferencementioning
confidence: 99%